Response of rumen microorganisms to pH during anaerobic hydrolysis and acidogenesis of lignocellulose biomass - Liang, Jinsong (Waste management (New York, N.Y.), 2024)
Copyright © 2023 Elsevier Ltd. All rights reserved.